Formability of AA 2219-O sheet under quasi-static, electromagnetic dynamic, and mechanical dynamic tensile loadings. (20th April 2021) - Su, Hongliang; Huang, Liang; Li, Jianjun; Xiao, Wang; Zhu, Hui; Feng, Fei; Li, Hongwei; Yan, Siliang
Abstract: The mechanism by which electromagnetic forming (EMF) enhances the formability of metals is unclear owing to the coupling effect of multi-physics fields. In the present work, the associated formability improvement mechanisms were qualitatively categorized and illustrated. This was realized by comparing the formability of fully annealed 2219 aluminum alloy (AA 2219-O) sheet under quasi-static (QS), electromagnetic dynamic (EM), and mechanical dynamic (MD) tensile loadings. It was found that the forming limit of AA 2219-O sheet under EM tensile loading was significantly (45.4%) higher than that under QS tensile loading, and was marginally (3.7%–4.3%) higher than that under MD tensile loading. In addition, the forming limit of AA 2219-O sheet demonstrated a negative dependency on the strain rate within the range of the dynamic tensile tests conducted. The deformation conditions common to EM and MD tensile loadings were responsible for the significant formability improvement compared with QS tensile loading. In particular, the inertial effect was dominant. The different deformation conditions that distinguish EM tensile loading from MD tensile loading resulted in the marginal improvement in formability. This was caused by the absence of a sustaining contact force at the later deformation stage and the lower strain rate. The body force exerted little influence on the formability improvement, and the thermal effect under the two dynamic tensile loadings was negligible.